Feline Sino-orbital Fungal Infection Caused by Aspergillus and Scopulariopsis - Amorim da Costa, Fernanda Vieira; Spanamberg, Andreia; Araujo, Ricardo; Werner, Juliana; Ferreiro, Laerte (Acta Scientiae Veterinariae, 2019)
Background: Deep fungal infections of the orbit and nasal passages causing rhinitis and ulcerative keratomycosis are uncommonly reported in cats. Hyalohyphomycetes and phaeohyphomycetes have rarely been associated with this disorder. Sino-orbital fungal diseases are emerging and more invasive than sino-nasal fungal diseases with poor response to therapy and a worse prognosis. Brachycephalic feline breeds seem to be at increased risk for development of upper respiratory fungal diseases. Diagnosis is based on the demonstration of fungal hyphae by cytology or histology and definitive confirmation by fungal culture and molecular methods. This is the first case report of a cat with clinical mixed fungal ball with Aspergillus and Scopulariopsis in Brazil. Case: A 3-year-old male Persian cat, in São José city, Santa Catarina, Brazil, was presented with exophthalmos and corneal ulcer of the left eye and protrusion, hyperemia, quemosis and fibroses of the left third eyelid. The retropulsion of the globe was negative in this eyeball and a presumptive diagnosis of a retrobulbar mass was made. The patient underwent a surgical procedure for inspection and collection of samples for bacterial and mycological culture. Culture revealed no bacterial growth, however, unique and abundant growth of Aspergillus spp. was present. A subconjunctival enucleation of the left eye was made and the mass was sent for histopathology examination. Histology showed inflammatory proliferative necrotizing pyogranulomatous reaction; with the presence of severe fungal infection evidenced by large number of hyaline septated regular and irregular mold hyphae. Molecular identification was performed using panfungal primers (ITS3-F / ITS4-R). Patient was treated with systemic itraconazole associated with amphotericin B and topical clotrimazole. A mass started to grow rapidly in the left pterygopalatine fossa and was surgically removed, but recurrence occurred seven days after. After 22 days of treatment, the animal died suddenly with a history of acute inspiratory dyspnea and cyanosis at the time prior to death. The diagnosis of sino-orbital fungal disease in the feline was based on clinical signs, mycological culture, histopathology and molecular methods. Discussion: Sino-orbital fungal diseases rare in cats and can result in significant injuries to the upper respiratory tract and eyes, sometimes resulting in enucleation and death. It seems feasible that a brachycephalic facial conformation may be an important risk factor for the development of sino-nasal fungal diseases in cats. Despite using selected drugs and eye enucleation to treat the disease, the cat developed a rapid growing oral mass that probably caused acute inspiratory dyspnea and death. Since no controlled studies exist on the treatment of feline fungal diseases, these cases are a challenge to the feline practitioner and this type of clinical manifestation should be included in the differential diagnosis of upper respiratory and ocular diseases.